ANALISIS STABILITAS TIMBUNAN DENGAN PLAXIS MEMBANDINGKAN 2 METODE AKIBAT KETERBATASAN LAHAN - Adhi, Bagas Wahyu; Setiyanto, Beni; Hidayawan, Ahmad; Rizani, Mohammad Debby (Universitas PGRI Semarang, 2023)
In the Cibitung - Cilincing Ramp 3-1 Toll Road development project, where the road alignment is an embankment construction with subgrade conditions that have dominant soil layers with sand and limited land. Then the implementation of subgrade improvement is carried out by comparing 2 methods, namely the first Replace 1.5 m (50 cm Limestone + Geomembrane + 50 cm Granular backfill + Geotextile Non Woven) + Sheet Pile with a length of 15 meters + Retaining Wall and the second Replace 1.5 m (50 cm Limestone + Geomembrane + 50 cm Granular backfill + Geotextile Non Woven) + Retaining Wall with Bore Pile D60 Int. 2 meters + Retaining Wall.The analysis of the two treatments used Plaxis with the results for the 1 year and 10 year consolidation of the two treatments meeting the requirements. The safety factor for the embankment slopes also meets the requirements. The results of the Horizontal Displacement in the first treatment are still very large, namely 6.73 cm, not in accordance with the AASTHO criteria of 3.8 cm and it can be seen from the profile bending moment on the Sheet Pile that the Sheet Pile is not pinched so that for this case the handling suitable is to use the second treatment, namely Replace 1.5 m (50 cm Limestone + Geomembrane + 50 cm Granular backfill + Geotextile Non Woven) + Retaining Wall with Bore Pile D60 Int. 2 meters + Retaining WallsÂ